Where in the World are GM crops planted? - Zambrano, Patricia; Wood-Sichra, Ulrike (International Food Policy Research Institute, 2016)
The infographic shows the visualization of national areas and type of GM crops planted in 2013 using Clive James ISAAA Brief 46 Global Status of Commercialized Biotech/GM Crops: 2013. It also uses World Bank (WDI 2014) income level classification. For detailed GM crop data, visit http://www.isaaa.org/resources/publications/briefs/46/default.asp